Citizens’s Association as Street Level Leadership: An Ethnography of Public Service in Surabaya's Urban Villages: Rukun Warga sebagai Street Level Leadership: Etnografi pelayanan publik di Kampung Kota Surabaya - Haryo Wibisono; Andra Pratama Juliyanto; Ahmad Yusroni; Yuni Lestari; Weni Rosdiana (Universitas Muhammadiyah Sidoarjo, 2026)
Studies on Rukun Warga (Citizens' Association) have not yet been viewed as a street-level leadership practice. This article aims to examine Rukun Warga leadership in public service through the Street Level Leadership theoretical framework. This framework is used to understand the relational leadership practices of RW (Neighborhood Unit) officials in carrying out public service activities in their neighborhoods. Using ethnographic methods with unstructured interviews and non-participant observation in three Rukun Warga areas in the Surabaya City area, this study examines the daily practices of activating administrative knowledge and decision-making discretion, and establishing a supportive community of residents. This study concludes the importance of relational leadership through administrative knowledge, community harmony as an output of public service.